Blessing or curse?: role of socially responsible human resource management in employee resilience - Zhang, Zhe (Journal of business ethics, 2025)
Extant studies have shown that socially responsible human resource management (SRHRM) brings beneficial effects on employees’ work outcomes. However, little attention has been given to the effect of SRHRM on employee resilience from a balanced perspective. This study draws on conversation of resources theory to examine how and when SRHRM influences employee resilience from a balanced perspective. Using two scenario-based experiments and one multi-wave field study, results show that SRHRM can enhance employee resilience by increasing work meaningfulness, but it can also deplete employee resilience by draining resources. Moreover, organization-set performance goal weakens the positive relationship between SRHRM and employees’ work meaningfulness. Organization-set performance goal also magnifies the positive relationship between SRHRM and employees’ resource depletion. This study presents theoretical and practical implications on how organizations can precisely promote employee resilience.